Haemophilia; Pattern of Clinical Presentation and Disease Severity - Qasim, Zahida; Naseem, Lubna; Asif, Naghmi; Hassan, Khalid (International Journal of Pathology, 2018)
Objective: To observe pattern of clinical presentation in patients of Hemophilia A and B.Materials and Methods: Fifty one patients of Haemophilia A and B were evaluated on the basis of Patient`s demographic data, history (family, medication, past) and parameters like age, clinical features(pallor, number of joint involved, ankylosis and pain). Blood complete picture, Coagulation screeningtests, bleeding time, PT, APTT, mixing studies and factor assays were documented.Results: In total of fifty one patients, twenty two (43.13%) had severe degree of disease (<1% factorconcentrate), while 19(37.2%) patients were diagnosed to have moderate degree of disease (factor concentrate1-5%) and 10 (19.6%) had mild disease (factor concentrate 5-50%). Patients having severe diseasewere diagnosed earlier than those having moderate and mild disease, and had frequent episodesof bleeding in soft tissues, joints, muscles etc.Conclusion: Pattern of clinical presentation helps to categories the haemophilia patients as havingmild, moderate or severe degree of disease